MAKNA SEMIOTIK DALAM PROSESI TEPUK TEPUNG TAWAR KELAHIRAN BAYI DESA SEDANAU TIMUR KECAMATAN BUNGURAN BATUBI KABUPATEN NATUNA - Tamarindi Sarifiandra, Gladys; Dody Irawan; Siti Habiba; Suhardi; Legi Elfitra; Tety Kurmalasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the semiotic meanings contained in the tepuk tepung tawar ritual performed during the birth of a baby in East Sedanau Village, Bunguran Batubi District, Natuna Regency. The research employs a qualitative descriptive method using an ethnographic approach. Data were collected through observation, in-depth interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The analysis is further interpreted using Charles Sanders Peirce’s semiotic theory, focusing on three types of signs: icons, indices, and symbols. The results show that the tepuk tepung tawar ritual contains various icons such as the use of mirrors and combing gestures, indices such as hair cutting and the application of tepung tawar water that indicate hopes for safety and well-being, and symbols such as black cloth, sugar, asam kandis, and salt, which represent protection, sweetness of life, resilience, and purification. These findings indicate that the ritual is not merely ceremonial but functions as a cultural system of meaning that reflects religious, social, and philosophical values within the Malay community of Natuna.